2021
DOI: 10.1101/2021.04.15.439986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence of an intracellular multiplication niche amongstAcinetobacter baumanniiclinical isolates

Abstract: The spread of antibiotic resistant Acinetobacter baumannii poses a significant threat to public health worldwide. This nosocomial bacterial pathogen can be associated with life-threatening infections, particularly in intensive care units. A. baumannii is mainly described as an extracellular pathogen with restricted survival within cells. This study shows that a subset of A. baumannii clinical isolates extensively multiply within non-phagocytic immortalized and primary cells, without the induction of apoptosis,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(55 reference statements)
1
0
0
Order By: Relevance
“…During the revision of this work, the Salcedo group reported that a subset of modern clinical isolates replicates within non-autophagic ACVs in epithelial cells [29]. In agreement with our results, large ACVs containing up to 50 bacteria were visualized in multiple non-phagocytic cells.…”
Section: Plos Pathogenssupporting
confidence: 90%
“…During the revision of this work, the Salcedo group reported that a subset of modern clinical isolates replicates within non-autophagic ACVs in epithelial cells [29]. In agreement with our results, large ACVs containing up to 50 bacteria were visualized in multiple non-phagocytic cells.…”
Section: Plos Pathogenssupporting
confidence: 90%